2009
DOI: 10.4049/jimmunol.0801854
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junctions at the Dendritic Cell-T Cell Interface Are Key Elements for Antigen-Dependent T Cell Activation

Abstract: The acquired immune response begins with Ag presentation by dendritic cells (DCs) to naive T cells in a heterocellular cell-cell contact-dependent process. Although both DCs and T cells are known to express connexin43, a gap junction protein subunit, the role of connexin43 on the initiation of T cell responses remains to be elucidated. In the present work, we report the formation of gap junctions between DCs and T cells and their role on T cell activation during Ag presentation by DCs. In cocultures of DCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…The essential role of Cxs and GJs regulating key immunological processes has become increasingly clear in recent years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although Cx43 expression in NK cells was first described over a decade ago (6), the role of Cx43 in NK cell function and activation remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential role of Cxs and GJs regulating key immunological processes has become increasingly clear in recent years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although Cx43 expression in NK cells was first described over a decade ago (6), the role of Cx43 in NK cell function and activation remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 expression has been described in different types of immune system cells, including neutrophils, dendritic cells (DCs), macrophages, NK cells, T cells, and B cells (5,6). Cxs and GJIC participate in key immunological processes, such as Ig secretion and cytokine production (7), transendothelial migration of leukocytes (8), peptide transfer and cross-presentation (9, 10), DC activation (11), regulatory T cell-mediated suppression through the transfer of cAMP (12), DC-mediated induction of IL-2 release, and proliferation of murine T cells (13). Recently, we showed that Cx43 accumulates at the immunological synapse (IS) during Ag-specific CD4 + T cell priming, mediating bidirectional crosstalk between DCs and T cells.…”
mentioning
confidence: 99%
“…cells crossed with Cx43 floxed mice, Kuczma and group set out to study the effect of Cx43 deletion in this lymphocyte population [47]. In contrast to the reports by Elgueta and team and Oviedo-Orta and colleagues [44,46] [44,46], no differences in CD4 ? effector T-cell proliferation were observed between wild-type lymphocytes and those lacking Cx43 using this model system [47].…”
Section: Connexin43 In Regulatory T-cellsmentioning
confidence: 66%
“…Using a TCR transgenic mouse model, dye coupling was detected between dye-loaded DCs and CD4 ? T-cells in vitro [44]. Dye coupling was detectable by 4 h of co-culture, reached a maximum at 8 h, and could be abolished by treatment with oleamide or a Cx43 mimetic peptide.…”
Section: Connexin43 In T-lymphocyte Activation and The Immunological mentioning
confidence: 90%
See 1 more Smart Citation